(untitled) (Revista de Ciências Agroveterinárias, 2021)
When not controlled efficiently, weeds in wheat crop stands may affect both the grain quality and yield production. This work aimed to assess the selectivity and efficacy of herbicides applied to control weeds in the wheat cultivar TBIO Sinuelo. Two experiments were set up to assess the selectivity and the efficacy of herbicides applied to wheat in randomized blocks design with four replications. Treatments tested were: iodosulfuron, pyroxsulam, metsulfuron-methyl, 2,4-D, clodinafop-propargyl, [bentazon + imazamox], saflufenacil, bentazon, carfentrazone-ethyl, imazamox, pendimethalin, [sulfentrazone + diuron], plus two control treatments, one weeded and the other infested. The greatest damages to wheat were caused by imazamox and the commercial mixture [bentazon + imazamox] with phytotoxicity of approximately 50%. On the other hand, applying the commercial mixture [sulfentrazone + diuron] allowed the highest wheat grain yield. The use of clodinafop-propargyl and pyroxsulam promoted the best control of Lolium multiflorum, with 100 and 98.25% at 21 days after treatment application, respectively. The control above 90% of Raphanus raphanistrum was reported with iodosulfuron, pyroxsulam, metsulfuron-methyl, 2,4-D, [bentazon + imazamox], saflufenacil, bentazon, and carfentrazone. Clodinafop-propargyl was the most efficient on ryegrass, and iodosulfuron, pyroxsulam, metsulfuron-methyl, 2,4-D, saflufenacil, and carfentrazone performed best on the turnip. Pyroxsulam was the treatment that showed, in both experiments, the best results for all-grain yield components, especially for grain yield.